The synthesis and characterization of N,N?-[4,4?-{ethane-1,2- di-yl-bis(oxy)bis(4,l-phenylene)}bis(N?-hydroxy)-2-(hydroxyimino) -acetimidamide], (LH4) and its Binuclear complexes - Duman, S.; Şekerci, M. (My University, 2009)
A novel vic-dioxime ligand (LH4) and its transition metal complexes with Cu(AcO)2·H2O, Ni(AcO) 2·4H2O, Co(AcO)2·4H2O and Cd(AcO)2 metal salts were synthesized. l,2-Bis(p-aminophenoxy) ethane reacted with anti-chloroglyoxime to give N,N?-[4,4?-{ethane- 1,2-di-yl-bis(oxy)bis(4,l-phenylene)}bis(N?-hydroxy)-2-(hydroxyimino) acetimidamide] (LH4) ligand. Ligand forms binuclear complexes [(LH3)2M2(AcO)2]·nH 2O with a 2:2 metal to ligand ratio, where M = Cu(II), Ni(II) and Cd(II), n = 2, 2 and 1, respectively. LH4 forms also binuclear Co(II) complex [(LH4)2Co2(AcO)4(H 2O)2]·2H2O with a metal to ligand ratio of 2:2. The Ni(II) and Cd(II) complexes are proposed to be tetrahedral while the Cu(II) and Co(II) complexes should be octahedral. Structural assignments are supported by a combination of elemental analyses, UV-Vis, IR and 1H-NMR spectra, magnetic measurements and TGA and DTA techniques.
Keywords: Transition metal complexes; Vic-oxime